2015
DOI: 10.1177/0731684415574538
|View full text |Cite
|
Sign up to set email alerts
|

Penetration impact resistance of novel tough steel fibre-reinforced polymer composites

Abstract: Conventional composites are susceptible to impact loading due to their low toughness. Novel annealed steel fibres possess a unique combination of high stiffness and high strain to failure. A range of composite laminates incorporating various steel fibre architectures with thermoplastic and thermoset matrices were produced and the low-velocity penetration impact resistance was characterized by falling weight impact tests, showing the high potential toughness of steel fibre composites. The effect of different pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Under compression load, various failure mechanisms (e.g., fiber fracture, interfiber failure, inter and intralaminar friction, fragmentation) additionally enable an excellent energy absorption capacity. Further investigations of Callens, [4] Mosleh et al, [2] or Lehmann et al [3] report similar improvements of the bending, impact and tensile behavior as a result of steel fiber integration into CFRP and proves the beneficial mechanical performance of this fiber hybrid material. In case of applications with special requirements, for example, regarding the reliability of operation, this can cause the exclusion of CFRP as construction material.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Under compression load, various failure mechanisms (e.g., fiber fracture, interfiber failure, inter and intralaminar friction, fragmentation) additionally enable an excellent energy absorption capacity. Further investigations of Callens, [4] Mosleh et al, [2] or Lehmann et al [3] report similar improvements of the bending, impact and tensile behavior as a result of steel fiber integration into CFRP and proves the beneficial mechanical performance of this fiber hybrid material. In case of applications with special requirements, for example, regarding the reliability of operation, this can cause the exclusion of CFRP as construction material.…”
Section: Introductionmentioning
confidence: 77%
“…Velocity at the transition of the fracture zone of influence to the remaining area x Displacement at the transition of the fracture zone of influence to the remaining area y Displacement of the specimen l 1 Length of the remaining area l 2 Length of the fracture zone of influence l 3 Total length of the laminate δ Newmark parameter β Newmark parameter v t See Equation (26) u t See Equation (27) Keywords analytical approach, hybrid composites, material model, post-failure behavior, steel fibers…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mosleh et al [22] showed that introducing steel fibers improves the impact resistance of carbon reinforced composites. McBride et al [18] studied energy dissipation and residual strain characteristics of hybrid and nonhybrid unidirectional (UD) glass/steel composites under cyclic tensile loads.…”
Section: Introductionmentioning
confidence: 99%
“…Though FRP composites show promise for application in various industries, the brittle nature of the fibers and limited capacity for energy absorption restrict the ability of the FRP to perform in critical structural elements that need protection from extreme events. Studies have investigated ways to improve the ductility of composites, and the incorporation of metal fibers into FRP composites for this purpose has been recently studied [ 10 , 11 , 12 , 13 , 14 , 15 ]. Metal fibers have high stiffness, high strength, ductile failure, high tensile energy absorption, high electrical conductivity, and superior structural integrity following impact [ 16 ].…”
Section: Introductionmentioning
confidence: 99%